Influence of winter rations and gains on subsequent pasture gains - Pickett, A.G.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
Five lots of good steer calves were used in this test which was started in the fall of 1946. Three lots were continued through two winters and two full grazing seasons. The other two lots were full fed as yearlings at the close of the first grazing season. The objects of the test were to use grass to the fullest extent, compare early summer gains with late season gains and to determine the value of feeding a protein supplement on bluestem grass after mid-summer. During the winter periods rations were designed to secure varying rates of gain in order that the influence of winter gains on summer gains might be determined. The comparison of feeds was incidental to the main purpose of this test.
Keywords: Beef; Gain; Bluestem pasture; Winter